Genetic zoning of the mineralization and its relationship with the extraction and recovery of minerals in the area of the Corona Deposit - Vereau Jave, José Enrique (2019)
The Corona deposit is one of the 14 known Tertiary deposits of Cu-Au-Mo and one of the 19 epithermal deposits of gold and silver located on the eastern slope of the western cordillera of the Andes, in the metallogenic province of Cajamarca (CMP) of northern Peru. Corona’s copper and gold deposit is typical of porphyry-type mineralization that includes stockworks structures of: (a) Potassium alteration, (b) sericite-chlorite-clay, (c) quartz-sericite-pyrite, (d) Orange clay (OC). As part of the development of the operations of the mine, two diamond drilling programs were carried out in 2010 and 2011 in the Corona pit, with the obtaining of witnesses or drill holes for their description and geological interpretation, where the alterations and mineralogical domains were identified. Each of the drillings that were extracted and with the subsequent geochemical sampling that helped to define and interpret the geology and geochemistry of each drill. This is how the Corona deposit is defined as a typical copper and gold porphyry deposit with an overprint of silica structures with high gold values, but also with contaminants.